A role for calcium‐dependent protein kinases in differential CO2‐ and ABA‐controlled stomatal closing and low CO2‐induced stomatal opening in Arabidopsis. Issue 5 (9th December 2020) - Schulze, Sebastian; Dubeaux, Guillaume; Ceciliato, Paulo H. O.; Munemasa, Shintaro; Nuhkat, Maris; Yarmolinsky, Dmitry; Aguilar, Jaimee; Diaz, Renee; Azoulay‐Shemer, Tamar; Steinhorst, Leonie; Offenborn, Jan Niklas; Kudla, Jörg; et al.
Summary: Low concentrations of CO2 cause stomatal opening, whereas [CO2 ] elevation leads to stomatal closure. Classical studies have suggested a role for Ca 2+ and protein phosphorylation in CO2 ‐induced stomatal closing. Calcium‐dependent protein kinases (CPKs) and calcineurin‐B‐like proteins (CBLs) can sense and translate cytosolic elevation of the second messenger Ca 2+ into specific phosphorylation events. However, Ca 2+ ‐binding proteins that function in the stomatal CO2 response remain unknown. Time‐resolved stomatal conductance measurements using intact plants, and guard cell patch‐clamp experiments were performed. We isolated cpk quintuple mutants and analyzed stomatal movements in response to CO2, light and abscisic acid (ABA). Interestingly, we found that cpk3/5/6/11/23 quintuple mutant plants, but not other analyzed cpk quadruple/quintuple mutants, were defective in high CO2 ‐induced stomatal closure and, unexpectedly, also in low CO2 ‐induced stomatal opening. Furthermore, K + ‐uptake‐channel activities were reduced in cpk3/5/6/11/23 quintuple mutants, in correlation with the stomatal opening phenotype. However, light‐mediated stomatal opening remained unaffected, and ABA responses showed slowing in some experiments. By contrast, CO2 ‐regulated stomatal movement kinetics were not clearly affected in plasma membrane‐targeted cbl1/4/5/8/9 quintuple mutant plants. Our findings describe combinatorial cpk mutants that function in CO2 control of stomatal movements and support the results of classical studies showing a role for Ca 2+ in this response.